Predicting prognosis in stable angina—results from the Euro heart survey of stable angina: prospective observational study. Issue 7536 (13th January 2006) - Daly, Caroline A; De Stavola, Bianca; Sendon, Jose L Lopez; Tavazzi, Luigi; Boersma, Eric; Clemens, Felicity; Danchin, Nicholas; Delahaye, Francois; Gitt, Anselm; Julian, Desmond; Mulcahy, David; Ruzyllo, Witold; et al.
Abstract: Objectives To investigate the prognosis associated with stable angina in a contemporary population as seen in clinical practice, to identify the key prognostic features, and from this to construct a simple score to assist risk prediction. Design Prospective observational cohort study. Setting Pan-European survey in 156 outpatient cardiology clinics. Participants 3031 patients were included on the basis of a new clinical diagnosis by a cardiologist of stable angina with follow-up at one year. Main outcome measure Death or non-fatal myocardial infarction. Results The rate of death and non-fatal myocardial infarction in the first year was 2.3 per 100 patient years; the rate was 3.9 per 100 patient years in the subgroup (n = 994) with angiographic confirmation of coronary disease. The clinical and investigative factors most predictive of adverse outcome were comorbidity, diabetes, shorter duration of symptoms, increasing severity of symptoms, abnormal ventricular function, resting electrocardiogaphic changes, or not having any stress test done. Results of non-invasive stress tests did not significantly predict outcome in the population who had tests done. A score was constructed using the parameters predictive of outcome to estimate the probability of death or myocardial infarction within one year of presentation with stable angina. Conclusions A score based on the presence of simple, objective clinical and investigative variables makes it possible to discriminate effectively between very low risk and very high risk patients and to estimate the probability of death or non-fatal myocardial infarction over one year.